Cucumber or grapes?—Context effects in multimedia learning - Seufert, Tina; Magner, Ulrike; von Randow, Jurij (Frontiers in Psychology, 2025)
IntroductionThe multimedia principle states that learning with text and pictures is better than learning with text only. It might also depend on the context, in particular on the material the neighbour is learning with - which might look much more interesting.MethodsTherefore, in our experiments (n = 48; 47) we analysed whether learning outcomes, situational interest and extraneous load depend on the learning material (text versus text with pictures) and the context (the neighbour learns with either the same or different material). In the second study, we additionally analysed the influence of the learner’s affective state. In particular, we analysed with concurrent hypotheses whether affect is a consequence of material and context, whether effects of material and context on learning outcomes and interest are mediated by negative affect, or whether negative affect prior to learning is a moderator of material and context effects.ResultsThe multimedia effect was replicated for all dependent variables. This is particularly interesting because in classical multimedia design studies the effect has only been shown for learning outcomes. The fact that the addition of pictures also has a positive effect on situational interest and on the experienced extraneous load is of additional interest. The interaction between material and context was significant for extraneous load (Exp.1) and for situational interest (Exp.2). The role of affect could not be clarified.DiscussionOverall, it seems relevant to consider not only the learning material, but also the context in which the material is provided. Even if the effects of context are not consistent for all learning parameters, situational interest was strongly influenced by context when inequality was particularly salient.